System and information quality an enabler for assessing ERP impacts on the public sector: The case of EPBT in Malaysian / Dahlia Fernandez Mohd Farid Fernandez, Zaini Zainol, Hawa Ahmad@Mutalib - Mohd Farid Fernandez, Dahlia Fernandez; Zainol, Zaini; Ahmad@Mutalib, Hawa (UiTM Cawangan Johor, 2019)
The aim of this study is to investigate the impact of the Enterprise Resource Planning (ERP) system on public sector performance in Malaysia using the DeLone and McLean Information System (IS) success model and four perspectives of Balanced Scorecard (BSC) measurement model, financial, customer, internal business, and innovation and learning. This study presents evidence gathered from a questionnaire survey of 52 local authorities (LAs) in Malaysia that have implemented the system. The data was collected by an electronically distributed Google Form questionnaire. The findings indicated that system quality is positive as predicted and significant for all perspectives of BSC. It was also found that information quality is positively related and significant in the customer perspective, and positively related but not significant in financial, internal business, and innovation and learning perspective in Malaysia. The results also ascertained that the implementation of the ERP system in LAs organisations leads to improved performance, proving the suitability of the system vis-à-vis the public sector. The results are expected to encourage other public sector units to adopt a similar strategy in order to gain benefits similar to those enjoyed by LAs.